2022
DOI: 10.3390/cells11081363
|View full text |Cite
|
Sign up to set email alerts
|

Organismal and Cellular Stress Responses upon Disruption of Mitochondrial Lonp1 Protease

Abstract: Cells engage complex surveillance mechanisms to maintain mitochondrial function and protein homeostasis. LonP1 protease is a key component of mitochondrial quality control and has been implicated in human malignancies and other pathological disorders. Here, we employed two experimental systems, the worm Caenorhabditis elegans and human cancer cells, to investigate and compare the effects of LONP-1/LonP1 deficiency at the molecular, cellular, and organismal levels. Deletion of the lonp-1 gene in worms disturbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 102 publications
0
20
0
Order By: Relevance
“…Here we show GRP78/BiP is a direct target of 2P‐Im in MM cells. Although prior studies have shown the third generation SOT, CDDO‐Methyl Ester (CDDO‐Me), can induce the UPR, and that inhibition of the UPR abrogates the induction of apoptosis by CDDO‐Me [27,28], the data presented here provide the first demonstration of a specific mechanism through which an SOT activates the UPR. CDDO‐2P‐Im induced apoptosis of human MM at nanomolar concentrations, and acted synergistically with the PI ixazomib, a second‐generation oral PI for the treatment of MM while being more tolerable compared with first generation PI [29].…”
Section: Introductionmentioning
confidence: 75%
“…Here we show GRP78/BiP is a direct target of 2P‐Im in MM cells. Although prior studies have shown the third generation SOT, CDDO‐Methyl Ester (CDDO‐Me), can induce the UPR, and that inhibition of the UPR abrogates the induction of apoptosis by CDDO‐Me [27,28], the data presented here provide the first demonstration of a specific mechanism through which an SOT activates the UPR. CDDO‐2P‐Im induced apoptosis of human MM at nanomolar concentrations, and acted synergistically with the PI ixazomib, a second‐generation oral PI for the treatment of MM while being more tolerable compared with first generation PI [29].…”
Section: Introductionmentioning
confidence: 75%
“…Lon protease has a significant influence on the aging process [ 147 , 148 , 149 ]. Reports have shown that deleting Pim1 in S. cerevisiae leads to faster aging [ 150 ] and C. elegans lonp-1 mutants had significantly shorter mean lifespan than wild type worms [ 151 ]. On the other hand, its overexpression in the filamentous ascomycete Podospora anserina extends health-span and lifespan [ 152 ].…”
Section: Lonp1 and Aging: A Role In Sarcopeniamentioning
confidence: 99%
“…Mitochondrial perturbation, accompanied by heat stress resistance was also observed in lonp-1 deficient C. elegans mutants [ 128 ]. LONP-1 is the worm homolog of human LonP1, a highly conserved mitochondrial protease that functions as a peptidase, a chaperone and a DNA-binding protein, thereby fulfilling its role as a central regulator of mitochondrial activity [ 129 ].…”
Section: Other Factors and Pathways That Aid Coping With Thermal Stressmentioning
confidence: 99%
“…In our recent study, we created a lonp-1 knockout C. elegans strain and showed that despite the disturbed mitochondrial function and impaired growth, fertility and lifespan in the mutant animals, there was a robust induction of both mitochondrial unfolded protein response (UPR mt ) and cytosolic HSR. Therefore, the lonp-1 mutant strain was significantly more thermotolerant compared to wild-type, even with the use of slightly aged (day 3 of adulthood) individuals [ 128 ]. However, the responsible factors and mechanisms, or the interplay between them, remains unclear.…”
Section: Other Factors and Pathways That Aid Coping With Thermal Stressmentioning
confidence: 99%